Clinical Presentation, Predictors, and Outcomes Among Mineralocorticoid Receptor Antagonist (MRA)-Eligible Acute Heart Failure Patients in the Heart Function Assessment Registry Trial in Saudi Arabia (HEARTS). (April 2018) - AlShamiri, Mostafa Q.; AlHabib, Khalid F.; AlHabeeb, Waleed; Raslan, Ismail R.; Ullah, Anhar; Elasfar, Abdelfatah A.; Alshaer, Fayez; Albackr, Hanan; Mimish, Layth; Almasood, Ali; AlGhamdi, Saleh; Ghabashi, Abdullah
Mineralocorticoid receptor antagonist (MRA) therapy is indicated after myocardial infarction in patients with acute heart failure (AHF) with an ejection fraction ≤40% and lacking contraindications. We analyzed clinical presentations, predictors, and outcomes of MRA-eligible patients within a prospective registry of patients with AHF from 18 hospitals in Saudi Arabia, from 2009 to 2010. For this subgroup, mortality rates were followed until 2013, and the clinical characteristics, management, predictors, and outcomes were compared between MRA-treated and non-MRA-treated patients. Of 2609 patients with AHF, 387 (14.8%) were MRA eligible, of which 146 (37.7%) were prescribed MRAs. Compared with non-MRA-treated patients, those prescribed MRAs more commonly exhibited non-ST-segment elevation myocardial infarction, acute on chronic heart failure, past history of ischemic heart disease, and severe left ventricular systolic dysfunction; were more commonly administered oral furosemide and digoxin; and had higher in-hospital recurrent congestive HF rates. Mortality did not significantly differ ( P > .05) between groups. In Saudi Arabia, 37.7% of eligible patients received MRA treatment, which is higher than that in developed countries. The lack of long-term survival benefit raises concerns about systematic problems, for example, proper follow-up and management after hospital discharge, warranting further investigation.